Social Class and Television Drama in Contemporary Britain
XVII, 271 p. 6 illus. in color.
Keywords: A rich and nuanced approach to class and its mediation through contemporary British television drama, this collection responds to the precarity that circulates and constricts in ‘Austerity Britain’, pre- and post-Brexit. The book self-consciously eschews obvious class-bound texts such as Shameless and Downton Abbey, offering fresh perspectives and insights on popular programmes such as This is England and Happy Valley. Although class is a central theme, the contributors also draw on theoretical work on emotion, gender and ethnicity. - - Kristyn Gorton, University of York, UK. This collection is a wide-ranging exploration of contemporary British television drama and its representations of social class. Through early studio-set plays, soap operas and period drama, the volume demonstrates how class provides a bridge across multiple genres and traditions of television drama. The authors tracethis thematic emphasis into the present day, offering fascinating new insights into the national conversation around class and identity in Britain today. The chapters engage with a range of topics including authorial explorations of Stephen Poliakoff and Jimmy McGovern, case studies of television performers Maxine Peake and Jimmy Nail, and discussions of the sitcom genre and animation form. This book offers new perspectives on popular British television shows such as Goodnight Sweetheart and Footballers’ Wives, and analysis of more recent series such as Peaky Blinders and This is England. .